L' ermite de Thèbes et Ie diable - Faerber, Robert (Apocrypha, 1998)
The legend is an original English composition written in the IXth century, based on the tales of the Desert hermits, and quite in line with the eschatological parenetic homiletic literature of the time. A devil is forced by a hermit to tell him about the terrors of hell and, being a fallen « angel », also of the joys of heaven. He does so by using a number of cliches drawn from Hibemo - English sources about the eschatological visions of the Other world - the Visio Pauli for instance - and by setting the elements of these visions into a number of quite original « hypothetical » scenarios. The legend was rather popular in England during the X-Xlth centuries, since quite a number of homelies used the one or the other of these scenarios.